P152 The Impact of a Selective oral TRPV1 Antagonist in Patients with Chronic Cough. (19th November 2012) - Smith, JA; Murdoch, RD; Newlands, A; Smart, K; Khalid, S; Kelsall, A; Holt, K; Dockry, R; Woodcock, A
Abstract : Background: Increased expression of TRPV1 receptors in the airways of chronic cough patients and heightened cough responses to inhaled capsaicin are suggestive of a role for TRPV1 receptors in chronic cough. We hypothesised that antagonism with a potent, selective, peripherally acting, oral TRPV1 antagonist, such as SB705498, would offer substantial cough symptom control. Methods: 21 patients with unexplained chronic cough (caucasian, 71% female, mean age 53yrs) participated in a double-blind, placebo-controlled, single dose, 2-period, crossover study to investigate the relationship between pharmacokinetic (PK) derived TRPV1 receptor occupancy, change in capsaicin (C5) threshold and 24hr cough count following 600mg SB705498. PK samples were taken over the dosing interval, capsaicin threshold was determined at screening, 2hrs (Cmax) and 24hrs post-dose and 24hr objective ambulatory cough counts were recorded on each dosing day via a cough monitor (vitaloJAK™) with manual counting. In addition, CQLQ and VAS urge to cough was measured. A battery of safety and tolerability measures were also recorded, including core body temperature. Results: TRPV1 receptor occupancy derived from plasma levels and factoring a plasma/lung ratio of 1, was approximately 45% at 2hrs and 25% at 24hrs. This translated to a 4 fold shift in the capsaicin C5 threshold at 2hrs (2uM to 8uM) maintained at 24hrs. However, there was no difference between hourly cough count profiles between placebo and SB705498 (see figure ), with hourly counts of 20–30c/h and the characteristic nocturnal reduction. Cough counts were remarkably stable, repeated one month apart and over the 8 months of the study (including winter). Conclusions: We conclude that despite a clear relationship between receptor occupancy and engagement of the TRPV1 receptor as evidenced by the shift in the capsaicin threshold, there was no translation to any clinical efficacy parameter. This suggests peripheral TRPV1 receptor activation is not an important determinant of spontaneous cough frequency in chronic cough and that reductions in capsaicin responses do not necessarily predict anti-tussive effects.